PROBLEMATIKA NIKAH SIRI DALAM PRESPEKTIF HUKUM POSITIF DAN ISLAM - Anna Dhifah, Muslikhah; Laila Fi Ramadhan, Sukma; Jabilirrohmah, Zaynab (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This study explores the legal and social implications of unregistered marriages (nikah siri) in Indonesia from the perspective of both Islamic law and national legislation. Using a qualitative library research method, the paper analyzes doctrinal sources, statutory regulations, and previous studies to identify the core issues affecting women and children in such marriages. Findings reveal that although nikah siri is religiously valid, its lack of legal recognition leads to significant problems, including loss of inheritance rights, unclear marital status, and vulnerability to domestic violence. The study also applies the Maqashid Syariah framework to assess how nikah siri disrupts key protections of religion, life, intellect, lineage, and property. As a solution, the paper recommends isbat nikah and legal registration of children’s birth certificates to harmonize religious and state law, ensuring justice and social welfare for affected families.